2014
DOI: 10.1063/1.4896676
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of resistive heating at graphene wrinkles and grain boundaries

Abstract: We directly measure the nanometer-scale temperature rise at wrinkles and grain boundaries (GBs) in functioning graphene devices by scanning Joule expansion microscopy with $50 nm spatial and $0.2 K temperature resolution. We observe a small temperature increase at select wrinkles and a large ($100 K) temperature increase at GBs between coalesced hexagonal grains. Comparisons of measurements with device simulations estimate the GB resistivity (8-150 X lm) among the lowest reported for graphene grown by chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 35 publications
(21 reference statements)
4
46
0
Order By: Relevance
“…On a grain-boundary scale, experimental evidence of this differential heating driven by crystallographic imperfections has been given by Grosse et al [132]. They investigated the grain boundary overheating in a pure graphene sheet at its grain boundaries.…”
Section: Proposed Mechanisms In Fsmentioning
confidence: 99%
“…On a grain-boundary scale, experimental evidence of this differential heating driven by crystallographic imperfections has been given by Grosse et al [132]. They investigated the grain boundary overheating in a pure graphene sheet at its grain boundaries.…”
Section: Proposed Mechanisms In Fsmentioning
confidence: 99%
“…For example, Joule expansion microscopy measurements have revealed strong Joule heating localized at graphene GBs, which can be many times larger than Joule heating in the grains. This has important implications for the reliability of graphene devices, as localized device failure could occur without a significant increase in the average device temperature [23]. Other measurements have shown that electrical noise is greatly enhanced by graphene GBs, which is detrimental for low-noise devices but may be useful for sensor applications [27].…”
Section: Electrical Resistivity Of Individual Gbsmentioning
confidence: 99%
“…GB [18][19][20][21][23][24][25][26][27]. The origin of this enhanced resistance has been probed with scanning tunneling spectroscopy (STS), and these measurements have revealed that GBs tend to be n-doped compared to the surrounding grains, such that they act as an electrical potential barrier to charge transport [40,41].…”
Section: Electrical Resistivity Of Individual Gbsmentioning
confidence: 99%
See 2 more Smart Citations